2017
DOI: 10.1167/iovs.16-20509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rates of Change of Lamina Cribrosa and Optic Nerve Head Surface Depths on Visual Field Progression in Glaucoma

Abstract: Citation: Wu Z, Lin C, Crowther M, Mak H, Yu M, Leung CK-S. Impact of rates of change of lamina cribrosa and optic nerve head surface depths on visual field progression in glaucoma. Invest Ophthalmol Vis Sci. 2017;58:182558: -183358: . DOI:10.1167 PURPOSE. To investigate the impact of the rates of change of anterior lamina cribrosa surface depth (ALCSD) and optic nerve head surface depth (ONHSD) on visual field (VF) progression in glaucoma. METHODS.One hundred forty-six eyes of 95 glaucoma patients had optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…[42][43][44][45][46] [Note: the anterior LC surface depth, ALCSD, is typically measured relative to a reference plane such as the Bruch's membrane (BM), its termination (BM opening [BMO]), or the choroidalscleral interface, CSI. [47][48][49][50] ] These LC differences measured by OCT are most apparent in glaucomatous eyes with a history of higher intraocular pressure (IOP) and for patients of relatively younger age. 45,46,48,[51][52][53] Recent evidence shows that greater LC depth and curvature are also predictive of faster glaucoma progression.…”
Section: Why Might These Retinal Oct Findings Occur More Frequently Imentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45][46] [Note: the anterior LC surface depth, ALCSD, is typically measured relative to a reference plane such as the Bruch's membrane (BM), its termination (BM opening [BMO]), or the choroidalscleral interface, CSI. [47][48][49][50] ] These LC differences measured by OCT are most apparent in glaucomatous eyes with a history of higher intraocular pressure (IOP) and for patients of relatively younger age. 45,46,48,[51][52][53] Recent evidence shows that greater LC depth and curvature are also predictive of faster glaucoma progression.…”
Section: Why Might These Retinal Oct Findings Occur More Frequently Imentioning
confidence: 99%
“…[47][48][49][50] ] These LC differences measured by OCT are most apparent in glaucomatous eyes with a history of higher intraocular pressure (IOP) and for patients of relatively younger age. 45,46,48,[51][52][53] Recent evidence shows that greater LC depth and curvature are also predictive of faster glaucoma progression. 54 In addition, OCT studies have confirmed and extended evidence that these LC structural differences are unique to glaucoma among optic neuropathies, particularly when matched for otherwise similar levels of VF damage and nerve fiber layer loss.…”
Section: Why Might These Retinal Oct Findings Occur More Frequently Imentioning
confidence: 99%
“…For example, in glaucoma research we may be interested in the association between optic nerve head surface depth (ONHSD) and visual field progression. Previous studies [12] have used joint models to explore this association by treating each eye as independent and modelling the association between the eye-specific longitudinal trajectory for ONHSD and the eye-specific event endpoint (visual field progression). However, this approach ignores the dependence between measurements taken on the two eyes clustered within a patient.…”
Section: Visual Field Progression In Glaucomamentioning
confidence: 99%
“…89 When the IOP in glaucomatous eyes was lowered after the introduction of medical therapy, 90 or after glaucoma filtration surgery, 91,92 a mean reduction in the anterior LCD was noted. In prospective studies of glaucoma patients, greater LCD was also associated with greater visual field progression 93 and faster rates of retinal nerve fibre layer (RNFL) thinning. 94 However, results with LCD have not always been consistent.…”
Section: Cribrosa On Optical Coherence Tomographymentioning
confidence: 99%